2019
DOI: 10.1097/sla.0000000000003540
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of High-risk Donor Livers After Ex Situ Resuscitation and Assessment Using Combined Hypo- and Normothermic Machine Perfusion

Abstract: Objective: The aim of this study was to evaluate sequential hypothermic and normothermic machine perfusion (NMP) as a tool to resuscitate and assess viability of initially declined donor livers to enable safe transplantation. Summary Background Data: Machine perfusion is increasingly used to resuscitate and test the function of donor livers. Although (dual) hypothermic oxygenated machine perfusion ([D]HOPE) resuscitates livers after cold storage, NMP enables assessment of hepatobiliary function. Methods: In a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
263
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 185 publications
(275 citation statements)
references
References 37 publications
8
263
3
1
Order By: Relevance
“…Van Leeuwen et al recently proposed a definition of viability criteria based on both hepatocellular (liver parenchyma) and cholangiocyte (bile duct) function (see section "Hypothermic followed by Normothermic Machine Perfusion"). 66 In addition, we hope that the results of the Viability Testing and Transplantation of marginal Livers (VITTAL study), an ongoing prospective clinical trial, can provide more information on the algorithm to decide which initially discarded liver should be transplanted (NCT02740608; ►Table 2). 67…”
Section: Normothermic Machine Perfusion In Experimental Studies Usingmentioning
confidence: 99%
“…Van Leeuwen et al recently proposed a definition of viability criteria based on both hepatocellular (liver parenchyma) and cholangiocyte (bile duct) function (see section "Hypothermic followed by Normothermic Machine Perfusion"). 66 In addition, we hope that the results of the Viability Testing and Transplantation of marginal Livers (VITTAL study), an ongoing prospective clinical trial, can provide more information on the algorithm to decide which initially discarded liver should be transplanted (NCT02740608; ►Table 2). 67…”
Section: Normothermic Machine Perfusion In Experimental Studies Usingmentioning
confidence: 99%
“…NMP is currently applied in an effort to resuscitate marginal liver grafts which would traditionally be declared as unfit for transplantation, or to extend the preservation period. [24][25][26] NMP can be performed immediately after procurement until transplantation, thus significantly minimizing SCS as the preservation modality for these grafts. 27 This procedure reduces IR injury.…”
Section: Normothermic Machine Perfusionmentioning
confidence: 99%
“…Given the physiological conditions maintained during NMP, donor livers typically resume normal metabolic and synthetic functions, such as lactate clearance, bile production, and synthesis of proteins soon after the initiation of NMP. 24,38 It is widely known that the liver is principally responsible for the synthesis of pro-and anticoagulant proteins along with the components of fibrinolytic system. However, the extent and rate of the synthesis of hemostatic proteins during ex situ NMP is yet to be thoroughly investigated.…”
Section: Hemostasis and The Prevention Of Coagulation Activation Durimentioning
confidence: 99%
“…The liver grafts used in this study were not transplanted after preservation; hence, post‐transplantation data are not available. Recent studies, however, showed that the use of NMP for viability assessment of otherwise discarded grafts was clinically feasible and also helped to define optimal criteria for the final acceptance of these rejected grafts once their viability had been re‐assessed . As a consequence, the clinical parameters for hepato‐cholangiocellular injury and function were used as mere viability markers to correlate with relative miR values .…”
Section: Discussionmentioning
confidence: 99%
“…hence, post-transplantation data are not available. Recent studies, however, showed that the use of NMP for viability assessment of otherwise discarded grafts was clinically feasible 13,22,39 and also helped to define optimal criteria for the final acceptance of these rejected grafts once their viability had been re-assessed. 22 In the case of bicarbonate in bile at 6 h NMP, also only CDmiR-222, and not HDmiR-122, at 2 h showed a strong, but negative, correlation (C), while both miRs were predictive of the bile/perfusate glucose ratio at 6 h (D).…”
Section: Thementioning
confidence: 99%